(3eSFhdjI GdTQWI Yf GdCVQGQ GdfGTFI Yf eRGhdI hXjaJgG (B/s - (3CMeO, YHO GdQGRb SjO eJhdjs ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI,s, 2021)
(3gPg GdOQGSI JYO ef GdOQGSGJ GdhUajI GdJMdjdjI GdQUOjI MjK Je GSJNOGe GdefgL GdhUaj GdJMdjdj hgh Pdc GdefgL GdPj jgOa Edi LeY GdMbGFb hGdHjGfGJ Yf XGgQI Ch CSdhH Yed eYjf Ch eTcdI eG aj eMGhdI dJaSjQ Pdc cGajG eY JMdjd Jdc GdHjGfGJ hGdhUhd Edi GdfJGFL GdeQLhI hcPdc GSJNOGe GdefgL GdQUOj hgh jbhe Ydi QUO GdXhGgQ hGdCNWGA GdJj JbY ef bHd GdLgGR GdEOGQj Ch eQab GdTQWI HUaI NGUI hQUO MGdGJ GdGfJgGcGJ GdJj JbY ef CaQGO gPG GdeQab CKfGA bjGege HCYeGdge hJhVjM GdaQb HjfgeG hHjf GdCNWGA GdJj JbY efge aj ZjQ ChbGJ Yedge ShGA cGfJ eTQhYI Ch ZjQ eTQhYI cPdc QUO hJhKjb GdCMOGK GdSdHjI hGdJj JNQL Yf GdbGfhf hPdc dJLfHgG hYOe JcQGQgG aj GdYed eQI CNQi MJi dG JUHM YQaG aj GdYed jSjQ Ydjg GdeQab(B.s
(3HHdjhLQGajI (B: (3UaMI (B649-707.s
Keywords: (3GdVHW GdEOGQjs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdTQWIs -- (3bhGfjf hJTQjYGJs -- (3eUQs